Antioxidant activity of anthocyanins from quixabeira (Sideroxylon obtusifolium) fruits - F.J. FIGUEIREDO; V.L.A.G. LIMA (Universidade Estadual Paulista, 2015)
ABSTRACT The fruits of Sideroxylon obtusifolium T.D. Penn. are small berries which have dark purple skin color at maturity due the anthocyanins presence. Therefore, the aim of this research was to evaluate the antioxidant activity of anthocyanins from mature fruits which were obtained at a semi-arid region of Paraiba/BR. In addition, the total anthocyanins content was measured by the pH differential method. The anthocyanins were purified by solid-phase extraction (SPE) using C18 Sep-Pak cartridges and submitted to antioxidant activity determined by scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH·). The butylated hydroxytoluene (BHT) was the positive control and the results were expressed as DPPH· scavenging activity (%). Anthocyanins content were higher in the husks (236.15 mg cyanidin-3-glucoside 100g-1 fw) than in the pulp (30.49 mg cyanidin-3-glucoside 100g-1 fw). The results showed that the potential free radical scavenging grew with the increase of concentration used and the reaction time. The ability of the anthocyanins in scavenging the free radical was statistically greater than the BHT one. The anthocyanins which were present in this fruit may supply substantial dietary source of antioxidant that may promote health and produce disease prevention effects or that could be applied in food industry as a good source of natural pigments